2015
DOI: 10.1111/gcbb.12265
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil carbon dioxide fluxes, soil organic carbon and microbial biomass carbon to biochar amendment: a meta‐analysis

Abstract: Biochar as a carbon-rich coproduct of pyrolyzing biomass, its amendment has been advocated as a potential strategy to soil carbon (C) sequestration. Updated data derived from 50 papers with 395 paired observations were reviewed using meta-analysis procedures to examine responses of soil carbon dioxide (CO 2 ) fluxes, soil organic C (SOC), and soil microbial biomass C (MBC) contents to biochar amendment. When averaged across all studies, biochar amendment had no significant effect on soil CO 2 fluxes, but it si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
187
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(216 citation statements)
references
References 93 publications
(118 reference statements)
20
187
2
7
Order By: Relevance
“…The results of meta-analysis conducted by He et al [47] also showed that biochar application significantly increased soil CO 2 fluxes by 22.14%. They discussed that the stimulation of soil CO 2 fluxes might be associated with the higher soil organic C status and the more active soil microbial activities since biochar application enhanced soil organic C and soil microbial biomass C [48]. The increase in CO 2 production upon biochar amendment was most likely due to mineralization of labile C fractions added with the biochar [49,50].…”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…The results of meta-analysis conducted by He et al [47] also showed that biochar application significantly increased soil CO 2 fluxes by 22.14%. They discussed that the stimulation of soil CO 2 fluxes might be associated with the higher soil organic C status and the more active soil microbial activities since biochar application enhanced soil organic C and soil microbial biomass C [48]. The increase in CO 2 production upon biochar amendment was most likely due to mineralization of labile C fractions added with the biochar [49,50].…”
Section: Co 2 Emissionsmentioning
confidence: 99%
“…It is uncertain whether the addition of biochar to soil increases (Castaldi et al ., ; Jones et al ., ; Mitchell et al ., ), does not affect (Zavalloni et al ., ) or even decreases (Lu et al ., ) soil respiration. Although these differences depend on either soil or biochar conditions or both (Liu et al ., ), changes in soil microbial communities might underpin the variation in soil respiration under biochar (Lehmann et al ., ). Jiang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although these CSA management practices have been widely used to enhance soil health (e.g., Denef, Zotarelli, Boddey, & Six, 2007;Fungo et al, 2017;Thomsen & Christensen, 2004;Weng et al, 2017), their effects on SOC sequestration are variable and highly dependent on experiment designs and site-specific conditions such as climate and soil properties (Abdalla, Chivenge, Ciais, & Chaplot, 2016;Liu et al, 2016;Paustian et al, 2016;Poeplau & Don, 2015). The potential to sequester soil carbon varies greatly among CSA practices, which has not been well addressed.…”
mentioning
confidence: 99%
“…The potential to sequester soil carbon varies greatly among CSA practices, which has not been well addressed. Also, most prior quantitative research focused on the effects of a single CSA practice on SOC (e.g., Abdalla et al, 2016;Liu et al, 2016;Poeplau & Don, 2015), very few studies estimated the combined effects of diverse CSA and conventional management practices. Also, most prior quantitative research focused on the effects of a single CSA practice on SOC (e.g., Abdalla et al, 2016;Liu et al, 2016;Poeplau & Don, 2015), very few studies estimated the combined effects of diverse CSA and conventional management practices.…”
mentioning
confidence: 99%